2004
DOI: 10.1787/hemp-v16-art19-en
|View full text |Cite
|
Sign up to set email alerts
|

Student Satisfaction in Higher Education

Abstract: Purpose: Customer satisfaction has been a goal within the services marketing area for many years. There has been considerable debate over whether higher education students are customers. Funding sources for higher education (HE), regard student satisfaction as one of the measurable components of a university's success in Australia. If it is accepted that HE students are indeed customers, then the marketing models that are applied to services marketing clients could also be applicable within the higher educatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 18 publications
0
30
1
4
Order By: Relevance
“…In light of attitudes towards learning effectiveness, a set of complex cognitive functions, emotions, and behavioral tendencies is represented (Aldemir & Gulcan, 2004). People's exposure to certain information induces a cognitive response that will affect attitude formation (Huang, Su, Zhou, & Liu, 2013 (Nijhuis, Segers, & Gijselaers, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In light of attitudes towards learning effectiveness, a set of complex cognitive functions, emotions, and behavioral tendencies is represented (Aldemir & Gulcan, 2004). People's exposure to certain information induces a cognitive response that will affect attitude formation (Huang, Su, Zhou, & Liu, 2013 (Nijhuis, Segers, & Gijselaers, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies which were carried out in Turkish sample (Terzioğlu & Yazıcı, 2003;Aldemir & Gülcan, 2004;Balcı & İlhan, 2006;Tekin et al, 2011;Sabbah & Aksoy, 2011;Sökmen, 2011;Arslan, 2014;Arslan & Altinbas-Akkas, 2014) also put forward similar dissatisfaction and underlined the importance of improving the facilities on campus climate and student retention. In this study, age group was a significant determinant of student satisfaction with campus sports and cultural facilities.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies (Kallio, 1995;Elliott & Healy, 2001;Wilkins et al, 2012) suggest that students' overall experience is strongly associated with campus climate, student-centeredness, campus social life and institutional effectiveness. Recent studies (Aldemir & Gülcan, 2004;Denson et al, 2010;Sojkin et al, 2012;de Jager and Gbadamosi, 2013;Sivis-Cetinkaya, 2013;Beck et al, 2014;Min & Koon, 2014;Zhang et al, 2014) found that female students tended to have more satisfaction than male counterparts, whereas a most recent work (Sarrico & Rosa, 2014) put forward that male students and freshmen were more satisfied groups. In Parahoo et al (2013)'s study, reputation of higher education institution was a contributing factor for both male and female students, while academic competence was significant for only males.…”
Section: Review Of Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…In Aldemir and Gülcan's (2004) Student Satisfaction Model, on the other hand, student satisfaction is explained by 4 factors: (1) Institutional factors (Academic factors, such as quality of education, communication with teachers in and outside the classroom, curriculum, course books and other teaching materials and instructors' evaluation of students; and Administrative factors, such as philosophy and practice of university administrators); (2) Extracurricular activities (in addition to the institution's all social, health, cultural and sporting activities, the services such as transportation and boarding that it can provide to the students, campus life); (3) Expectations (students' own preferences and expectations about the faculty); and (4) Demographic factors.…”
Section: Theories and Modelsmentioning
confidence: 99%